Correlation between API 50 CH and multiplex polymerase chain reaction for the identification of vaginal lactobacilli in isolates - Brolazo, Eliane Melo; Leite, Domingos Silva; Tiba, Monique Ribeiro; Villarroel, Marina; Marconi, Camila [UNESP]; Simoes, Jose Antonio (Sociedade Brasileira de Microbiologia, 2011)
Identification of Lactobacillus sp. strains by phenotypic methods may lead to doubtful results possibly interfering in the reliability of the epidemiological and probiotics studies. Therefore this study aimed to determine the best methodology for the identification of the large diversity of lactobacilli species found in the vagina by comparing two techniques, one based on their biochemical profile and other employing molecular biology. A carbohydrate fermentation test (API 50 CH) was compared with multiplex polymerase chain reaction (PCR) for the identification of species of vaginal lactobacilli from 135 healthy women. The kappa index was used to evaluate agreement between the methods. Using the molecular technique, L. crispatus (32.6%), L. jensenii (25%) and L. gasseri (20.6%) were the most frequent species. However, using the biochemical technique, the most frequent species were: L. acidophilus (34.8%), L. crispatus (27.2%) and L. fermentum (13%). Although L. acidophilus was the most frequent specie found by biochemical tests, no strain of this microorganism was detected by PCR. Agreement between the methods was low for identification of all the most common species. Although rates of L. crispatus detected were similar using both methods (32.6% and 27.2%), agreement between them was relatively low (kappa = 0.52). Conclusions: Our results confirmed the limitation of the biochemical method and the applicability of a previously published molecular method (Multiplex PCR) for the identification of lactobacilli in the vaginal tract, focusing on further necessity of its improvement for also targeting L. vaginalis and L. iners.
Keywords: carbohydrate fermentation test; multiplex PCR; identification; vaginal lactobacilli; vaginal ecosystem